Organizational and methodological principles for improving the psychophysical training of cadets of higher education institutions with specific learning conditions - Kosheleva , Olena; Velykyi , Yurii (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The preparation of students of higher education for future professional activities is a system of organizational and pedagogical measures aimed at the formation and improvement of professionally important qualities, skills, and abilities necessary for successful work in the chosen specialty. Researchers have repeatedly drawn attention to the fact that graduates of higher education institutions do not reach the required level of psychophysical readiness for the future profession. Such a situation requires finding ways to increase the effectiveness of psychophysical training of future specialists. At the same time, the issue of improving the psychophysical training of cadets of higher education institutions with specific learning conditions is particularly acute, since their professional activity is often associated with a risk to health and life, and requires a high level of physical conditions, the development of mental qualities necessary for high-quality performance of tasks as assigned. The purpose of the study research is to develop and scientifically substantiate the organizational and methodological principles of improving the psychophysical training of the cadets of higher education institutions with specific training conditions, which carry out the training of police officers. Research materials and methods. 120 cadets of the Dnipropetrovsk State University of Internal Affairs took part in the study. During the research, the following methods were used: analysis and generalization of scientific and methodological literature and documentary materials, pedagogical observation, sociological methods (surveys, questionnaires). The results of the study show that the factors that reduce the effectiveness of psychophysical training of cadets of higher education institutions with specific learning conditions are: long duration of the school day, increase in the number of hours students spend at the desk, high emotional stress; the use of authoritarian teaching methods; lack of individual approach. To solve this problem, we suggest taking into account the individual and typological features of the higher nervous activity of the students when choosing means, methods of physical education, and determining the amount of physical exertion. Conclusions: taking into account the individual and psychological characteristics of cadets in the process of psychophysical training will contribute to increasing the effectiveness of all forms of classroom and extracurricular activities, the cognitive activity of future police officers, and the formation of their motivation for physical and mental self-improvement.